(untitled) (Journal of the College of Basic Education, 2022)
The present study includes the isolation and identification of hundred isolates of different bacterial species were isolated from 200 patients with burn infection in Numan hospital in Baghdad city/Iraq. All isolates identified depending on morphological, cultural and biochemical tests and the results showed that the P. aeroginosa was the most common injuries burns with percentage 35% , followed by K. peumoniae, S. aureus , E. coli (30%, 20%,15%) respectively and the susceptibility of the above isolates to nine antibiotics were tested, the results showed that the Ciproflaxacin and streptomycin were the highest effective antibiotics with a percentage 52.75%, 51.75% respectively, while all of the isolated bacteria were resistant to trimethoprim 95.25% and variable susceptibility to other antibiotics. As well as the antibacterial activity of aqueous and alcoholic extracts of Punica granatum peels were studied against all isolated bacteria and the results found that the MIC of aqueous and alcoholic extracts were ranged between 80-140mg/ml and 40- 80 mg/ml, While the inhibition zone were ranged between 11-18 mm and 9- 22 mm respectively . Furthermore, the results of the in vivo assay showed that the treatment of mice with the 100mg/ml of aqueous extract and Chloramphenicol have more effectiveness than other concentrations and the number of bacteria P. aeroginosa was reduced significantly (P≤0.001) during the treatment days .